2018
DOI: 10.1097/md.0000000000010473
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ENST00113 promotes proliferation, survival, and migration by activating PI3K/Akt/mTOR signaling pathway in atherosclerosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The results showed that the appropriate concentration of β-elemene promotes the viability of motor neurons, which can be blocked by PI3K or AKT inhibitors. Numerous studies have demonstrated that cell proliferation can be induced through the PI3K-AKT-mTOR signaling pathway [35,36]. Similarly, our results showed that the phosphorylation of PI3K, AKT, and mTOR is induced by β-elemene, revealing that β-elemene promotes VSC4.1 motor neuronal proliferation through the PI3K-AKT-mTOR signaling pathway under normal conditions.…”
Section: Discussionsupporting
confidence: 62%
“…The results showed that the appropriate concentration of β-elemene promotes the viability of motor neurons, which can be blocked by PI3K or AKT inhibitors. Numerous studies have demonstrated that cell proliferation can be induced through the PI3K-AKT-mTOR signaling pathway [35,36]. Similarly, our results showed that the phosphorylation of PI3K, AKT, and mTOR is induced by β-elemene, revealing that β-elemene promotes VSC4.1 motor neuronal proliferation through the PI3K-AKT-mTOR signaling pathway under normal conditions.…”
Section: Discussionsupporting
confidence: 62%
“…21,22 For instance, Yao et al reported that lncRNA ENST00113 positively regulated cell growth and survival by mediating the PI3K/Akt/mTOR axis in AS. 23 Zhang et al conrmed that lncRNA TUG1 depletion promotes AS by regulation of the miR-133a level. 24 Pan demonstrated that lncRNA H19 enhances AS development through modulating the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al showed that lncRNA H19 promotes atherosclerosis by increasing the activity of the MAPK and NF-κB signaling pathways and suppressing apoptosis [37]. Yao et al reported that lncRNA ENST00113 promotes cell proliferation, survival, and migration by activating the PI3K/Akt/mTOR signaling pathway in atherosclerosis [38]. In the present study, a lncRNA target pathway network was constructed to explore the role of lncRNAs in the signaling pathways of atherosclerotic progression.…”
Section: Discussionmentioning
confidence: 94%